2020
DOI: 10.1101/2020.08.17.254284
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The immune landscape of primary central nervous system diffuse large B cell lymphoma

Abstract: Primary central nervous system diffuse large B-cell lymphoma (PCNSL) is a rare and aggressive entity that resides in an immune-privileged site. The tumor microenvironment (TME) and the disruption of the immune surveillance influence lymphoma pathogenesis and immunotherapy resistance. Despite growing knowledge on heterogeneous therapeutic responses, no comprehensive description of the PCNSL TME is available. We investigated the immune subtypes of PCNSL and their association with molecular signaling and survival… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…The TME and methods of tumor immune evasion in lymphomas arising in immune sanctuaries are distinct from systemic DLBCL, an example being the loss of HLA class I and II expression on PCNSL cells (72). To further elucidate the immune contexture of PCNSL, Alame et al (73) used bulk RNA sequencing analysis to highlight three distinct immune cell signatures with high, intermediate or low immune gene expression levels; PCNSL tumors lacking an immune-rich TME correlated with inferior clinical outcomes. This study also demonstrated clinically relevant immune checkpoint ligandreceptor interactions, with high PD-L1-expressing tumor associated macrophages (TAMs) and high TIM-3 expression associated with an immune-rich TME and improved outcomes.…”
Section: Primary Central Nervous System Lymphomamentioning
confidence: 99%
“…The TME and methods of tumor immune evasion in lymphomas arising in immune sanctuaries are distinct from systemic DLBCL, an example being the loss of HLA class I and II expression on PCNSL cells (72). To further elucidate the immune contexture of PCNSL, Alame et al (73) used bulk RNA sequencing analysis to highlight three distinct immune cell signatures with high, intermediate or low immune gene expression levels; PCNSL tumors lacking an immune-rich TME correlated with inferior clinical outcomes. This study also demonstrated clinically relevant immune checkpoint ligandreceptor interactions, with high PD-L1-expressing tumor associated macrophages (TAMs) and high TIM-3 expression associated with an immune-rich TME and improved outcomes.…”
Section: Primary Central Nervous System Lymphomamentioning
confidence: 99%
“…Next-generation sequencing analysis has indicated that genes associated with the cytoskeleton, cell adhesion, the extracellular matrix, and matrix metalloprotease were predictors of prognosis (9). Transcriptomics analysis has revealed three immune subtypes in PCNLS: immune rich, poor, and intermediate; patients in the immune rich group had a hyperactivation of STAT3 signaling and inflammatory signaling such as interferon-g and tumor necrosis factor-a and had a longer progression-free survival (PFS) than those in the immune intermediate or immune poor group (10).…”
Section: Introductionmentioning
confidence: 99%